Violência na atenção primária à saúde de Belo Horizonte: o que pensam e fazem os profissionais de saúde - Taciana Malheiros Lima Carvalho (2015)
The violence is a complex phenomenon that affects all the people, it has multiple causes, it suffers the interference from social and cultural factors and it has increased much in national and international scopes. The insertion of the subject of the violence in health represents a challenge for the organization of the jobs, the Primary Attention to Health, carries of input of especially the system, as well as for the professionals who act in it. This study aimed to investigate the occurrence of violence in the Primary Attention to the Health of Belo Horizonte city in the perspective of the workers of the teams of family health. This study is about qualitative and exploratory research type, which used semi structuralized interviews. Three centers of health, inserted in different areas of social and sanitary risk as index of vulnerability in health used in the city were searched.The results pointed out the agreement of the violence as a complex question of multiple conceptualizations; the majority of the professionals feels prepared to deal with the subject; actions of boarding of the violence are carried out in the daily of the activities teams; the promotion to health as the main attribution of the health center in relation to the subject; the perception that it is possible to prevent violence.